Comparison of the Immulok cultureset kit and virus isolation for detection of herpes simplex virus in clinical specimens. - Hayden, F G (1983)
The Immulok test performed at 24 h after inoculation had a 73% sensitivity and 97.5% specificity for detecting herpes simplex virus in clinical specimens, as compared with viral culture in human embryonic lung fibroblasts. The test increased the proportion of positive specimens reportable at 24 h by 48% (P less than 0.01) but failed to detect 4 of 31 (13%) specimens positive for cytopathic effect at 24 h and 13 of 32 (41%) specimens positive at greater than or equal to 48 h after inoculation.